Synthesis of Oligoesters Plastic Film from Polylactic Acid with Mono Ester Plasticizer of Wood Flour and Rice Bran and its Hydro Degradation - Edwin Azwar (Jurnal Rekayasa Proses, 2014)
Composites of polylactic acid (PLA) with mono ester plasticizer (MEP) from wood flour and rice bran were prepared to evaluate the effect of MEP filler content on the mechanical, functional, thermal, and morphological properties of the composites and its degradation. The SEM study provided evidence that there was sufficient interfacial adhesion between the PLA matrix and the MEP from wood flour and rice bran filler. This was likely a result of mechanical interlocking among them. An addition of 10 and 30% MEP from wood flour or rice bran resulted in an improvement of strain and tensile properties of the composite. The composites of PLA and MEP from wood flour and rice bran experienced degradation through hydrolysis of regions that have crystalline structure. Keywords: polylactic acid, fiber, cellulose, wood flour, rice bran Komposit dari polylactic acid (PLA) dan mono ester plasticizer (MEP) dari tepung kayu dan bekatul disiapkan untuk mengevaluasi pengaruh jenis bahan isian MEP terhadap sifat mekanis, fungsi, sifat termal, dan morfologis komposit tersebut beserta reaksi degradasinya. Hasil analisis dengan SEM menunjukkan bahwa terdapat interfacial adhesion yang cukup besar antara matriks PLA dan MEP dari tepung kayu dan bekatul, yang dapat disebabkan oleh mechanical interlocking antara keduanya. Penambahan 10 dan 30% MEP tepung kayu dan bekatul menyebabkan perbaikan regangan (strain) dan tegangan tarik (tensile). Komposit PLA dan MEP dari tepung kayu dan bekatul mengalami degradasi dengan hidrolisis pada bagian yang berstruktur kristal. Kata kunci: polylactic acid, serat, selulosa, tepung kayu, bekatul